(3QSGdI GdHdGZ hGdfgGjI aj GdJhMjO Edi cGaI GdehMOjf GdeJHQFjf ef GdJdMjOs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s ((3MeRI Hf Ydi Hf CMeO s)
(3ChdgG (B:s
(3JCdja YHO ehdGfG Ld PcQg gGOi GdeSJLjHjf GdefJbe ef GdeTQcjf HSja ehdGfG Ld PcQg QaY fSNJgG Edi GdMUQI GddGghJjI s
(3BNQgG (B:s
(3hGdMeO dehdGfG hMOg dGTQjc dg hMSHfG Gdehdi hfYe GdfUjQ GdeYjf JeJ QSGdI GdHdGZ hGdfgGjI HMeO ehdGfG hefg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds